Littoral resources, food chain length and top predator size - Are these connected with lake size? - Kankaala, Paula; Kahilainen, Kimmo K.; Olin, Mikko; Rissanen, Antti J. (Elsevier, 2024)
The size of a lake ecosystem sets many direct and indirect physical limits for habitats available for different food web compartments as well as the taxa inhabiting these. We tested the hypotheses that 1) reliance of fish on littoral resources increase in lakes with shoreline development, and 2) food chain length and 3) top predator size increase with lake size. We analyzed food web trophic structure, based on stable isotope analyses (SIA) of carbon (δ13C) and nitrogen (δ15N), in six boreal lakes in southern and eastern Finland (area 0.13–567 km2). We also applied data from gillnet monitoring of two common predatory fish, perch (Perca fluviatilis) and pike (Esox lucius), in >100 lakes as well as data from national large pike (weight > 10 kg) competition. Our results based on SIA did not support the first two hypotheses. Mixing-model results indicated great contribution of littoral resources for many fish, however, showing considerable within-taxa variation for some species. Fish reliance on littoral resources was not directly related to lake shoreline development. The lakes had four trophic levels and large predators coupled both littoral and pelagic habitats. The very rare freshwater pinniped, Saimaa ringed seal (Pusa hispida saimensis), shared the same trophic position with piscivorous fish. However, we found some support for the third hypothesis. The maximum size of perch was positively correlated with lake size, and the majority (88 %) of very large pikes (>10 kg) were caught from lakes with the area > 1 km2, indicating habitat size importance for large predators.
Keywords: stable isotopes; fish size; habitat coupling; trophic structure; pike; perch